ENDINGS OF NOUNS AND ADJECTIVES - Navruzova Farida Nazarovna (Western European Studies, 2024)
The article describes the phenomenon of desubstantivation of nouns of adjective declension. It is shown that the linguistic basis of desubstantivation is the internal form of these nouns. The author examines occasional and usal desubstantivation, analyzes the structuralsemantic varieties of initial nouns and adjectives formed on their basis.
Keywords: substantivation; desubstantivation; occasional; noun